2012
DOI: 10.1002/jbm.a.34451
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term in vitro responses of human peripheral blood monocytes to ferritic stainless steel fiber networks

Abstract: Beneficial effects on bone-implant bonding may accrue from ferromagnetic fiber networks on implants which can deform in vivo inducing controlled levels of mechanical strain directly in growing bone. This approach requires ferromagnetic fibers that can be implanted in vivo without stimulating undue inflammatory cell responses or cytotoxicity. This study examines the short-term in vitro responses, including attachment, viability, and inflammatory stimulation, of human peripheral blood monocytes to 444 ferritic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…It was observed that cell attachment at early time points was associated solely with the surfaces and junctions of the metal fibers. 9,11 Similar findings were observed in the networks used in the present study as illustrated in Figure 2c. However, theoretically the optimal region for transduction of strain to cells in vivo lies within interfiber spaces as depicted in Figure 1a.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It was observed that cell attachment at early time points was associated solely with the surfaces and junctions of the metal fibers. 9,11 Similar findings were observed in the networks used in the present study as illustrated in Figure 2c. However, theoretically the optimal region for transduction of strain to cells in vivo lies within interfiber spaces as depicted in Figure 1a.…”
Section: Discussionsupporting
confidence: 90%
“…The present study builds upon earlier work with these stainless steel grades in fully dense form 8 and as fiber networks. 9,11 These earlier studies established the suitability of these fiber networks for in vitro cell culture with a range of different cell types, including human mesenchymal stem cells and osteoblasts. It was observed that cell attachment at early time points was associated solely with the surfaces and junctions of the metal fibers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The diagonal length of the fibre cross-sectional area was about 40 µm. Details on the manufacturing of these networks are described elsewhere [40,41]. Information on the 444 and 316L networks are presented in Table 2 [41,42].…”
Section: Substrates -Fibre Networkmentioning
confidence: 99%
“…If the strains generated in the surrounding tissue lie in the beneficial range, bone cell growth will be promoted [3]. Cell responses to these networks have been assessed using human osteoblasts [4] and peripheral blood monocytes [5]. Metal fibre networks of this type [6] exhibit good mechanical properties even at high porosity levels as compared to typical open-cell metallic foams [7], whose properties are often very poor partly due unavoidable stress localization effects by severe inhomogeneities and gross defects and by the presence of embrittling constituents in the cell walls.…”
Section: Introductionmentioning
confidence: 99%